A new maximum power point tracking algorithm for ocean wave energy converters. (April 2017) - Lettenmaier, Terry; von Jouanne, Annette; Brekken, Ted
Highlights: A new "cycling" maximum power point tracking (MPPT) algorithm is presented. This algorithm is compared to a perturb and disturb algorithm described in previous literature. Ocean test results of a WEC are presented for both algorithms. Computer simulation results for a different WEC are presented for both algorithms. Abstract: This paper describes a new maximum power point tracking (MPPT) algorithm developed to control a wave energy converter (WEC) in random seas. This algorithm, named the cycling MPPT algorithm, is compared to a perturb and observe algorithm described in numerous literature. Both algorithms were initially tested during 2012 ocean tests of the half-scale prototype Wave Energy Technology – New Zealand (WET-NZ) WEC off the Oregon coast. During these sea trials the perturb and observe algorithm failed to provide effective control of the WET-NZ, while the cycling algorithm was observed to give effective control. More complete investigations were later carried out using MATLAB-Simulink simulations of an autonomous WEC (AWEC) being developed at Oregon State University. The results of the AWEC simulations also showed the cycling algorithm provided better control than the perturb and observe algorithm. The operation of the cycling algorithm was fully characterized during the AWEC simulations and these results are presented.